Training On Making Plant Pots from Coconut Husks to Strengthen the Entrepreneurship of PKK Women in Ngestiharjo Village, Boyolali (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Limited skills in entrepreneurship and the processing of creative products are among the factors hindering economic growth in the community. The objective of this community service activity is to enhance the knowledge and technical skills of the PKK women of Ngestiharjo Village in the production of innovative plant pots made from coconut husks. The training method employed is participatory learning, combining brief theoretical instruction with hands-on practice (learning by doing). The activity began with a presentation on the utilization of coconut husks, followed by a demonstration of pot-making techniques, and independent practice by participants with intensive guidance. The activity was conducted in several stages, including a basic training stage on processing coconut husks into plant pots, covering cleaning, shaping, drying, and product finishing techniques. The results showed that the skill mastery rate reached 90%, exceeding the 80% target, and an N-Gain value of 0.61, which falls into the moderate-to-high category, providing empirical evidence that the participatory learning method with a “learning by doing” approach is effective when applied to the target group of PKK women. The products produced by the participants demonstrated adequate quality with a sufficiently diverse and attractive range of designs. It is concluded that this program has yielded tangible results through a transformation in the participants’ entrepreneurial mindset, marked by the emergence of independent home-based production initiatives, marketing exploration via social media, and the formation of a cooperative business group under the auspices of the Ngestiharjo Village PKK.
Keywords: Community Economy; Entrepreneurship; Plant Pots; Coconut Husk